Attitude, Learning Motivation, and The Usage of Learning Source and Mastering English of Students in MAN 1 Metro - Sutarmin Sadewo; Hery Yufrizal (Jurnal Ilmiah ESAI, 2011)
This study aims at finding out the influences of three variables (motivation learning attitude, and learning source implementation toward students’ achievement in English at MAN 1 Metro. The method used in this research is ex-post de facto involving three independent variables and one dependant variable. The population is all the students of XI class, social program in MAN 1 Metro. The sample is taken by using proportional random sampling system involving 59 students which 50% of 157 populations. The result of research and data analysis shows that there are significant correlations between the three independent variables and the dependant variable. The data show that (1) there is a significant correlation between students’ attitude toward the lesson, and their English Achievement (correlation coefficient (ryx1) 0,694). (2) There is a significant correlation between students’ motivation and their English Achievement (correlation coefficient (ryx2) 0,765).  (3) There is a significant correlation between the implementation of learning resource and the students English Achievement (correlation coefficient (ryx3) 0,548). Therefore, it is suggested that the teachers raise students’ motivation and improve their attitude toward learning English. Due to the high importance of learing reasources to help students improve their ability in English, the school is suggested to provide learning resources. Key words: attitude, motivation, source of learning, English Achievement